DISTRIBUTIONS GENERATED WITH BOUNDARY VALUES OF FUNCTIONS OF THE SPACE \(H^p\), \(1 ≤ p < ∞\) - Manova-Eraković, Vesna (Matematichki Bilten, 2000)
In this work are given necessary and sufficient conditions for a regular distribution in \(D'\) to be distribution generated with a boundary function of some function from the space \(H^p\), \(1 ≤ p < ∞\).